Effects of Moringa oleifera leaves on hemoglobin and serum retinol levels and underweight status among adolescent girls in rural Bangladesh - Khanam, Mansura; Sanin, Kazi Istiaque; Ara, Gulshan; Sultana Rita, Razia; Boitchi, Anika Bushra; Farzana, Fahmida Dil; Haque, Md. Ahshanul; Ahmed, Tahmeed (Frontiers in Nutrition, 2022)
Objectives Moringa oleifera has been used for centuries due to its medicinal properties and health benefits. The plant has antifungal, anti-viral, and anti-inflammatory properties. We aimed to evaluate the effect of consumption of Moringa leaves, along with a regular diet on serum hemoglobin and retinol and underweight status among rural Bangladeshi adolescent girls. Methods This school-based quasi-experimental study involved 226 adolescent girls (12–14 years-old). Intervention group (n = 113) received a meal comprising rice, concentrated dal, and fried potato with Moringa pakora (oil-fried snack); the control group (at a different school in an adjacent area with similar population demographics) received calorie-matched meal without Moringa pakora for 6 months. We used generalized liner regression (GLM) analysis, to explore the effect of the intervention among the groups between baseline and endline. Results Mean age of the intervention and control groups were 12.7 ± 0.7 and 13.3 ± 0.8 years, respectively. After adjusting for maternal education, absenteeism, asset index, BMI-for-age Z-score, GLM regression showed significant positive changes in hemoglobin (intervention vs. control: coef = 0.41, P = 0.010) and serum retinol (coef = 0.27, P = 0.00). No significant changes in weight was observed between groups. Conclusion Consumption of Moringa leaves has the potential to improving hemoglobin and serum retinol level and should be encouraged as regular diet.